Debt financing: Does it boost or hurt firm performance in product markets? - Campello, Murillo (Journal of Financial Economics, 2006)
Previous research seeks to establish whether debt boosts or hurts a firm's product market performance. This paper proposes that both of these outcomes can be observed: debt can boost and hurt performance. I first model a nonmonotonic relation between debt-like finance and competitive conduct. I then empirically examine the within-industry relation between leverage and sales performance using data from 115 industries over 30 years. My tests deal with the endogeneity of debt in a novel fashion: I use creditors’ valuation of assets in liquidation to identify financial leverage. I find that moderate debt taking is associated with relative-to-rival sales gains; high indebtedness, however, leads to product market underperformance.